A systematic review of elements in game-based Arabic language learning framework for dyslexic children - Mohamed Masrop, Noor Azli; Zainudin, Ghazali; Nadzri, Einannabella; Md Yunus, Asrina Suriani; Sahrir, Muhammad Sabri; Syed Sahuri, Sarifah Nurhanum (Universiti Sultan Zainal Abidin, 2023)
Game-Based Language Learning (GBLL) has been proven an effective approach tool to improve learning and has become a widely used teaching aid to maintain engagement and motivation in learners. The purpose of this systematic literature review is to identify the framework elements of Game-Based Arabic Language Learning (GBALL) for Dyslexic Children. Although previous research has addressed various guidelines and frameworks for educational tools in Arabic language learning, however, only few studies focus on dyslexic children. The methodology used in this paper is Systematic Literature Review (SLR) by Kitchenham (2004) and Kitchenham and Charters (2007). A selection of relevant research was performed to achieve the research objectives. The selected online open sources databases involved as are primary resources: Google Scholar, ResearchGate, UM Student Repository, Open Access Theses and Dissertation (OATD). Scientific publications and journals, conference proceedings, and technical papers are found in well-known online databases that include a complete citation and reference analysis. Based on a systematic review process, the researchers reported and discussed findings with possible future research directions. A total of 18 studies were selected,which revealed two themes: the multimedia elements of game-based language learning for dyslexic children and the Arabic language learning elements for dyslexic children. The results of this study can be applied as a guideline for educational tools for dyslexic children in Arabic language learning.